Heat transfer characteristics of fullerene and titania nanotube nanofluids under agitated quench conditions - Jaimon, Dennis Quadros; Khan, Sher Afghan; Prashanth, T.; Mogul, Yakub Iqbal; Hanumanthraya, R; Abbas, Mohammad; Saleel, Ahamed; Shaik, Saboor (American Chemical Society, 2022)
Distilled water and aqueous fullerene nanofluids having concentrations of 0.02, 0.2, and 0.4 vol % and titania (titanium dioxide, TiO2) nanofluids of 0.0002, 0.002, and 0.02 vol % were analyzed for heat transfer characteristics. Quenching mediums were stirred at impeller speeds of 0, 500, 1,000, and 1,500 RPMs in a typical Tensi agitation system. During the quenching process, a metal probe made of ISO 9950 Inconel was used to record the temperature history. The inverse heat conduction method was used to calculate the spatial and temporal heat flux. The nanofluid rewetting properties were measured and matched to those of distilled water. The maximum mean heat flux was 3.26 MW/m2, and the quickest heat extraction was 0.2 vol % fullerene nanofluid, according to the results of the heat transfer investigation.